2019
DOI: 10.1007/s00213-019-05376-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol on sequential decision-making biases during gambling

Abstract: Luke (2019) The effects of alcohol on sequential decision-making biases during gambling. Psychopharmacology. pp. 1-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
0
7
1
Order By: Relevance
“…Another common way to take more risks in gambling is to increase the stake size, which increases the variance in the potential outcomes (i.e., one definition of 'risk'). Using gambling-like tasks, 4 laboratory studies found increases in stake sizes following losses (Bibby, 2016;Bibby and Ross, 2017) and losing streaks (Studer et al, 2015;Tobias-Webb et al, 2020), as an expression of within-session loss-chasing.…”
Section: Intensificationmentioning
confidence: 99%
“…Another common way to take more risks in gambling is to increase the stake size, which increases the variance in the potential outcomes (i.e., one definition of 'risk'). Using gambling-like tasks, 4 laboratory studies found increases in stake sizes following losses (Bibby, 2016;Bibby and Ross, 2017) and losing streaks (Studer et al, 2015;Tobias-Webb et al, 2020), as an expression of within-session loss-chasing.…”
Section: Intensificationmentioning
confidence: 99%
“…In addition, the symptoms of cognitive distortion can also be controlled with the Schema Therapy approach as demonstrated by Navidi Poshtiri et al ( 2022) on nursing and midwifery students with health anxiety, Malik et al (2021) on young adults with borderline personality features and Pourpashang and Mousavi (2021) on clients under substance dependence treatment. Besides, there are also studies that show the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) in treating cognitive distortions such as studies on emotional exhaustion in women with multiple sclerosis (Dizaj et al, 2022), MBCT intervention as a population-level strategy for anxiety and depression (Burgess et al, 2021), and also on reducing gambling-related craving (Melero Ventola et al, 2020) The concept of cognitive distortion has long been explored and adopted; although it was originally used in the framework of cognitive therapy in mental health issues (Ciccarelli et.al., 2020;Younesi et.al., 2015), it has now been applied in various forms such as general antisocial behavior (Chabrol et al, 2014;Demeter & Rad, 2020;Wallinius et al, 2011), criminal behavior such as drug use (Kirisci et al, 2004) and sexual offences (Paquette et al, 2020;Pornari et al, 2021;Soldino et al, 2020;Szumski et al, 2018), health areas such as hearing and speech problems (Colucci, 2016), alcohol consumption (O' Leary-Barrett et al, 2017;Tobias-Webb et al, 2020), psychological trauma (Chung & Shakra, 2022;Vallath et al, 2020), and eating disorders (Mehak & Racine, 2020;Moreno et al, 2014;Powers et al, 1999). Not only that, the concept of cognitive distortion also appeals to researchers on the ground of economic and finance (Boldizzoni, 2013;Kuljamina et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of cognitive distortion has long been explored and adopted; although it was originally used in the framework of cognitive therapy in mental health issues (Ciccarelli et.al., 2020; Younesi et.al., 2015), it has now been applied in various forms such as general antisocial behavior (Chabrol et al, 2014; Demeter & Rad, 2020; Wallinius et al, 2011), criminal behavior such as drug use (Kirisci et al, 2004) and sexual offences (Paquette et al, 2020; Pornari et al, 2021; Soldino et al, 2020; Szumski et al, 2018), health areas such as hearing and speech problems (Colucci, 2016), alcohol consumption (O’Leary-Barrett et al, 2017; Tobias-Webb et al, 2020), psychological trauma (Chung & Shakra, 2022; Vallath et al, 2020), and eating disorders (Mehak & Racine, 2020; Moreno et al, 2014; Powers et al, 1999). Not only that, the concept of cognitive distortion also appeals to researchers on the ground of economic and finance (Boldizzoni, 2013; Kuljamina et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in some cases, OFGs and MMGs have exhibited greater levels of gambling harm than ONGs, indicating that on its own, simply gambling online may not be a substantial risk factor for problematic gambling behaviour. For example, Blaszcynski et al (2016) found that OFGs and MMGs were more likely than ONGs to report using alcohol while gambling -a behaviour associated with increased engagement in risky gambling (Cronce & Corbin, 2010;Tobias-Webb et al, 2020;Welte et al, 2004). MMGs also tend to participate in a greater number of gambling activities than ONGs and OFGs (Gainsbury et al, 2015b;Hing et al, 2022;Leppink et al, 2016;Lind et al, 2021) -which is also linked to an increased risk of problematic gambling (Dowling et al, 2017).…”
Section: Introductionmentioning
confidence: 99%